In vitro delayed response to dihydroartemisinin of malaria parasites infecting sickle cell erythocytes - Albert A. Gnondjui; Offianan A. Toure; Berenger A. Ako; Tossea S. Koui; Stanislas E. Assohoun; Eric A. Gbessi; Landry T. N’Guessan; Karim Tuo; Sylvain Beourou; Serge-Brice Assi; Francis A. Yapo; Ibrahima Sanogo; et al. (Malaria Journal, 2024)
Abstract Background Decreased efficacy of artemisinin-based combination therapy (ACT) for Plasmodium falciparum malaria has been previously reported in patients with sickle cell disease (SCD). The main purpose of this study was to investigate the in vitro susceptibility of isolates to dihydro-artemisinin (DHA) to provide a hypothesis to explain this treatment failure. Methods Isolates were collected from patients attending health centres in Abidjan with uncomplicated P . falciparum malaria. The haemoglobin type has been identified and in vitro drug sensitivity tests were conducted with the ring stage assay and maturation inhibition assay. Results 134 isolates were obtained. Parasitaemia and haemoglobin levels at inclusion were lower in patients with haemoglobin HbSS and HbSC than in patients with normal HbAA. After ex vivo RSA and drug inhibition assays, the lowest rate of parasitic growth was found with isolates from HbAS red cells. Conversely, a significantly higher survival rate of parasites ranging from 15 to 34% were observed in isolates from HbSS. Isolates with in vitro reduced DHA sensitivity correlate with lower RBC count and haematocrit and higher parasitaemia at inclusion compared to those with isolates with normal DHA sensitivity. However, this decrease of in vitro sensitivity to DHA was not associated with Kelch 13-Propeller gene polymorphism. Conclusion This study highlights an in vitro decreased sensitivity to DHA, for isolates collected from HbSS patients, not related to the Pfkelch13 gene mutations. These results are in line with recent studies pointing out the role of the redox context in the efficacy of the drug. Indeed, SCD red cells harbour a highly different ionic and redox context in comparison with normal red cells. This study offers new insights into the understanding of artemisinin selective pressure on the malaria parasite in the context of haemoglobinopathies in Africa.